Breathable fabric-based triboelectric nanogenerators with open-porous architected polydimethylsiloxane coating for wearable applications. (15th December 2022) - Tan, Di; Xu, Bingang; Gao, Yuanyuan; Tang, Yun; Liu, Yufang; Yang, Yujue; Li, Zihua
Abstract: Triboelectric nanogenerators (TENGs), which can harvest low-frequency mechanical energy from human activities, are potential for wearable electronics, especially textile-based TENGs. Besides triboelectric performance, wearable comfort, like air permeability, is crucial for wearable electronics. However, the textile-based TENGs integrated with high performance and wearable comfort still remain challenging. Here, we construct the open porous architected PDMS coatings on fabric for breathable fabric-based TENG (oPF-TENG) based on the synergistic effect of insoluble NaCl, DBP and soluble silicone oil. The open porous structure constitutes the airflow channel with the air permeability of ∼73 mm/s. Meanwhile, the porous structure and the PVDF filler enhance the triboelectric output. The open circuit voltage, short circuit current and power density of oPF-TENG reach ∼600 V, ∼15 μA and 5.67 W/m 2, respectively. The as-made oPF-TENG with good air permeability and triboelectric output can not only contribute to the human body energy harvesting but also show potential for wearable self-powered sensing. Graphical Abstract: A breathable fabric-based triboelectric nanogenerator based on open porous architected PDMS coatings is designed. The sacrificial templates, including insoluble NaCl, DBP and soluble silicone oil, were applied to construct the open porous structures synergistically. The open porous structures enhance both the triboelectric output and air permeability, guaranteeing triboelectric performance and wearable comfort simultaneously. The as-made TENG with good air permeability and triboelectric output can not only contribute to the human body energy harvesting but also show potential for wearable self-powered sensing. ga1 Highlights: A breathable fabric-based TENG with open-porous PDMS coatings was designed. Synergistical effect of pore-forming agents contributes open porous structures. Open porous structure enhances both the triboelectric output and air permeability. The oPF-TENG integrates stable triboelectric performance and wearable comfort.